Effects of pinealectomy and exogenous melatonin on ghrelin and peptide YY in gastrointestinal system and neuropeptide Y in hypothalamic arcuate nucleus: Immunohistochemical studies in male rats - Aydin, Mehmet; Canpolat, Sinan; Kuloglu, Tuncay; Yasar, Abdullah; Colakoglu, Neriman; Kelestimur, Haluk (Elsevier, 2008)
It is reported that the pineal gland and its main hormone melatonin may have a role in the regulation of ghrelin synthesis in the brain. Stomach is the place where ghrelin is predominantly expressed and secreted. One aim of this study was to investigate possible effects of pinealectomy and melatonin treatment on gastric ghrelin amount. The studies on the effects of the pineal gland on leptin and ghrelin arises the question whether the pineal gland has also effects on the other energy-regulatory peptides such as peptide YY (PYY) and neuropeptide Y (NPY). Therefore, we also aimed to investigate the changes in the immumohistochemical staining of intestinal PYY and hypothalamic NPY following pinealectomy and melatonin treatment. Serum PYY levels were also investigated. Sprague-Dawley rats were divided into four groups as sham-operated (SHAM), sham-operated with melatonin treatment (SHAM-MT), pinealectomised (PNX) and melatonin-treated PNX (PNX-MT) groups. The cells immumostained for ghrelin were abundant throughout the gastric mucosa in all the groups. Neither pinealectomy nor exogenous melatonin affected significantly ininumohistochemical staining of ghrelin in stomach. Pinealectomy resulted in a significant increase in immunohistochemical staining of PYY in ileum. The results of serum PYY measurement corresponded closely to the data obtained by immunohistochemical analysis of PYY in ileum, being significantly lower and higher in SHAM and PNX groups, respectively. Pinealectomy caused a decrease in NPY synthesis in ARC as understood from low immunohistochemical staining of NPY. Melatonin treatment increased NPY synthesis in SHAM rats and restored reduction in NPY synthesis caused by pinealectomy. In conclusion, the pineal gland and its main hormone melatonin can be suggested to have a role in the regulation of NPY synthesis in ARC and PYY in gastrointestinal system. (C) 2007 Elsevier B.V All rights reserved.
Keywords: pinealectomy; melatonin; ghrelin; peptide YY; neuropeptide Y